Systematic Review and Meta-Analysis of Lysine-Specific Demethylase 1 Expression as a Prognostic Biomarker of Cancer Survival and Disease Progression. (1st October 2021) - Agboyibor, Clement; Dong, Jianshu; Effah, Clement Y.; Drokow, Emmanuel K.; Pervaiz, Waqar; Li, Dié; Kang, Lei; Ma, Xinli; Li, Jian; Liu, Zhenzhen; Liu, Hong-Min
Background: Numerous studies on the prognostic significance of lysine-specific demethylase 1 (LSD1) up-regulation in tumors have different outcomes. The inconsistency originated from various studies looking into the association between LSD1 and tumor cells has prompted the decision of this quantitative systematic review to decipher how up-regulated LSD1 and overall survival (OS) or recurrence-free survival (RFS) or disease-free survival (DFS) are linked in tumor patients. Methods: Articles were searched from online databases such as Embase, Web of Science Core, PubMed, Google Scholar, and Scopus. The extraction of the hazard ratios (HR) with their 95% confidence intervals ( CIs ) was attained and survival data of 3151 tumor patients from 17 pieces of related research were used for this meta-analysis. Results: To shed light on the link between LSD1 up-regulation and the prognosis of diverse tumors, the pooled hazard ratios (HRs) with their 95% confidence intervals ( CIs ) were determined. In this meta-analysis, it was observed that LSD1 up-regulation is linked with poor OS (HR = 2.08, 95% CI : 1.66–2.61, P < .01) and RFS (HR = 3.09, 95% CI : 1.81–5.26, P < .01) in tumor patients. However, LSD1 up-regulation was not linked to DFS (HR = 1.49, 95% CI : .83–2.69, P = .18) in tumor patients. The subcategory examination grouped by tumor type and ethnicity showed that LSD1 up-regulation was linked with a poor outcome in the esophageal tumor and hepatocellular carcinoma and Asian patients, respectively. For clinical-pathological factors, up-regulated LSD1 was significantly linked with Lymph node status. Conclusion: Despite the shortfall of the present work, this meta-analysis proposes that LSD1 up-regulation may be a prognostic biomarker for patients with tumors including esophageal tumors and hepatocellular carcinoma. We propose that large-scale studies are vital to substantiate these outcomes.